Discovery of novel dual acetylcholinesterase and butyrylcholinesterase inhibitors using machine learning and structure-based drug design - Tripathi M.K.; Bhardwaj B.; Waiker D.K.; Tripathi A.; Shrivastava S.K. (My University, 2025)
Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are crucial targets that catalyse the breakdown of acetylcholine (ACh) and are implicated in the pathogenesis of Alzheimer's disease (AD). Thus, the development of cholinesterase (AChE and BChE) inhibitors with a novel scaffold is an effective way to intervene in the pathogenesis of AD. This study used a multistep virtual screening method combined with machine learning (ML) models and structural bioinformatics to identify a novel dual acetylcholinesterase and butyrylcholinesterase inhibitor from the Maybridge database. Finally, five common hits (AW00462, AW00794, MWP01235, SCR00709, CD05692) were found after a consensus analysis of classification models and multistep screening protocol which showed their potential against AChE and BChE enzymes. Further, MM/GBSA free energy calculation and MD simulation studies predicted CD05692 as a potential inhibitor, which formed stable interactions with the active site residues compared with the other compounds. The docking score of CD05692 was found maximum negative (AChE= -15.03 Kcal/mole; BChE= -7.07 Kcal/mole) compared with the other identified hits. The MM/GBSA binding free energy ∆G (AChE= -76.34 Kcal/mole; BChE= -74.72 Kcal/mole) and the HOMO orbital energy (-0.352,410 eV) was also predicted to be in favour of CD05692. The in silico pharmacokinetic investigations also ascertained its drug likeliness properties. Finally, compound CD05692 was synthesised, characterized and evaluated in vitro for ChE (hAChE and hBChE) inhibitory potential. The IC50 value of the lead CD05692 has shown good hAChE inhibition (IC50 = 0.927 ± 0.019 µM) and moderate hBChE inhibition (IC50 = 6.377 ± 0.038 µM). Thus, based on this study, we proposed that CD05692 could further be optimized as a lead to design potential cholinesterase inhibitors to combat AD. © 2023 Elsevier B.V.